Is rapid automatized naming automatic? - Georgiou, George K.; Stewart, Blair (Preschool and Primary Education, 2013)
According to Segalowitz and Segalowitz (1993), a process becomes automatic when the mean response time, its standard deviation, and the coefficient of variation (standard deviation/mean response time) decrease across time. To examine whether rapid automatized naming (RAN) reflects automatic processing, we retrospectively traced the development of RAN pause time, its standard deviation, and the coefficient of variation from Kindergarten to Grade 3. Twenty-five good readers and twenty-five poor readers were assessed on RAN Colors and Digits and their sound files were analyzed. The results indicated that there was a significant decrease across time in pause time and its standard deviation for both groups of readers. However, the coefficient of variation increased across time. In addition, the correlations between the pause time and the coefficient of variation were negative. These findings suggest that the observed improvement in RAN performance across time is not due to increased automaticity, but rather due to improved efficiency in the operation of each RAN sub-process.